2013
DOI: 10.1186/1743-0003-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the contribution of the ankle and hip joints to multi-segmental balance control

Abstract: BackgroundHuman stance involves multiple segments, including the legs and trunk, and requires coordinated actions of both. A novel method was developed that reliably estimates the contribution of the left and right leg (i.e., the ankle and hip joints) to the balance control of individual subjects.MethodsThe method was evaluated using simulations of a double-inverted pendulum model and the applicability was demonstrated with an experiment with seven healthy and one Parkinsonian participant. Model simulations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 48 publications
3
101
0
3
Order By: Relevance
“…In some exercises, human skeleton-based assessment can be very useful to the physician, such as during cane height assessment, balancing tests such as double-leg stance and single-leg stance [18], and even finger-to-nose task performance tests [19]. The user can select the joints to be tracked and plot the corresponding depth information on a graph.…”
Section: Detecting and Tracking Of Multiple Jointsmentioning
confidence: 99%
“…In some exercises, human skeleton-based assessment can be very useful to the physician, such as during cane height assessment, balancing tests such as double-leg stance and single-leg stance [18], and even finger-to-nose task performance tests [19]. The user can select the joints to be tracked and plot the corresponding depth information on a graph.…”
Section: Detecting and Tracking Of Multiple Jointsmentioning
confidence: 99%
“…The application of the perturbation of the leg and trunk segment makes it possible to investigate the dynamics of the hip and ankle joint and their coupling (Boonstra et al 2013;Engelhart et al 2014b). …”
Section: Applicationmentioning
confidence: 99%
“…Previous research already showed that it is possible to describe underlying mechanisms involved in standing balance using perturbations and multi-input-multi-output closed loop system identification techniques (MIMO-CLSIT) (Boonstra et al 2013;Engelhart et al 2014b;Peterka 2002). In those studies, several systems were perturbed one by one during quiet stance, while the subject kept his balance.…”
Section: Introductionmentioning
confidence: 99%
“…The newly developed techniques are based on a concept from the field of system identification: the application of external (mechanical) perturbations to 'open' the closed loop of motor control (Ljung, 1999;Pintelon and Schoukens, 2001). Previously this approach has successfully been applied to identify different types of reflexes in posture control (van der Helm et al, 2002;Schouten et al, 2008;Mugge et al, 2010) and to separate the contribution of the legs and joints involved in upright balance control (van Asseldonk et al, 2006;Pasma et al, 2012;Boonstra et al, 2013).…”
Section: Aim and Outline Of This Thesismentioning
confidence: 99%